2023
DOI: 10.1098/rsos.231427
|View full text |Cite
|
Sign up to set email alerts
|

Pre-fertilization gamete thermal environment influences reproductive success, unmasking opposing sex-specific responses in Atlantic salmon ( Salmo salar )

Marco Graziano,
Monica F. Solberg,
Kevin A. Glover
et al.

Abstract: The environment gametes perform in just before fertilization is increasingly recognized to affect offspring fitness, yet the contributions of male and female gametes and their adaptive significance remain largely unexplored. Here, we investigated gametic thermal plasticity and its effects on hatching success and embryo performance in Atlantic salmon ( Salmo salar ). Eggs and sperm were incubated overnight at 2°C or 8°C, temperatures within the optimal thermal range of this species. Cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…However, when embryos were incubated at high temperatures, those sired by sperm treated at high temperatures exhibited inferior performance. In contrast, Ritchie and Marshall (2015) and Graziano et al (2023) suggested that the adaptive effects of tubeworm ( Galeolaria gemineoa ) and salmon ( Salmo salar ) sperm exposure when the offspring condition aligns with the condition of sperm exposure, hinting at the epigenetic mechanisms at play. On the contrary, Kekäläinen et al (2018) present evidence of maladaptive effects on European whitefish ( Coregonus lavaretus ) offspring resulting from sperm experiences, further complicating the overall picture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when embryos were incubated at high temperatures, those sired by sperm treated at high temperatures exhibited inferior performance. In contrast, Ritchie and Marshall (2015) and Graziano et al (2023) suggested that the adaptive effects of tubeworm ( Galeolaria gemineoa ) and salmon ( Salmo salar ) sperm exposure when the offspring condition aligns with the condition of sperm exposure, hinting at the epigenetic mechanisms at play. On the contrary, Kekäläinen et al (2018) present evidence of maladaptive effects on European whitefish ( Coregonus lavaretus ) offspring resulting from sperm experiences, further complicating the overall picture.…”
Section: Discussionmentioning
confidence: 99%
“…These alterations in sperm may confer advantages to offspring when they encounter similar conditions to those experienced by the sperm (Figures 1 A & B). This introduces the anticipatory hypothesis, suggesting that offspring are primed for anticipated conditions, enhancing their performance in such conditions (Burgess & Marshall, 2014; Graziano et al, 2023; Hosken et al, 2003; Marshall, 2015; Ritchie & Marshall, 2013). However, if conditions differ from those experienced by the sperm, offspring performance may not improve, as the modifications may not prove advantageous in the new context (Lymbery et al, 2021).…”
Section: Introductionmentioning
confidence: 99%